IMPLEMENTASI KEBIJAKAN BANTUAN LANGSUNG TUNAI DANA DESA BAGI MASYARAKAT MISKIN YANG TERDAMPAK COVID-19 DI DESA SIDOREJO KECAMATAN SAWAHAN KABUPATEN NGANJUK - Abror, Daimul (Universitas Kadiri, 2021)
This research describes, analyzes and interprets the implementation of the Village Fund Cash Direct Assistance Policy for the community in Sidorejo village, especially the poor community during the Covid-19 outbreak. The research method used is a qualitative method with a case study approach. The results of the research are that (1) the implementation of policies in the decision mentality approach from the village government is related to the determination of residents who are entitled to receive BLT Village Funds based on the results of village deliberations involving the Village Head and BPD. In addition, it is also based on provisions from the central government that BLT DD recipients are not PKH participants, but the reality on the ground is that there are still many PKH recipients who receive BLT DD. This attitude shows that there is a mentality that shows that the village government is less careful in data collection and on the other hand the mentality of the people who like to take advantage of this momentum to increase personal benefits. (2) the implementation of the policy in the system approach approach shows that the flow and mechanism of data collection have been carried out in accordance with applicable regulations, where the phase I distribution system of village funds has been running well. (3) the implementation of the policy in the collaborative network approach shows that there is still a lack of understanding between the Village Government as the implementer of the BLT DD policy and the community as the recipient of the BLT DD, where there are still people who are participating in the PKH program who in fact still receive BLT DD. This shows a lack of awareness from the community and on the other hand the lack of a validation process from the village government.